Achromatic Cues Are Important for Flower Visibility to Hawkmoths and Other Insects - van der Kooi, Casper J.; Kelber, Almut (Frontiers in Ecology and Evolution, 2022)
Studies on animal colour vision typically focus on the chromatic aspect of colour, which is related to the spectral distribution, and disregard the achromatic aspect, which is related to the intensity (“brightness”) of a stimulus. Although the chromatic component of vision is often most reliable for object recognition because it is fairly context independent, the achromatic component may provide a reliable signal under specific conditions, for example at night when light intensity is low. Here we make a case for the importance of achromatic cues in plant-pollinator signalling, based on experimental data on naïve Deilephila elpenor and Macroglossum stellatarum hawkmoths, optical modelling and synthesising published experiments on bees, flies, butterflies and moths. Our experiments show that in ecologically relevant light levels hawkmoths express a strong preference for brighter stimuli. Published experiments suggest that for flower-visiting bees, butterflies, moths and flies, achromatic cues may be more important for object detection than often considered. Our optical modelling enabled disentangling the contribution of pigments and scattering structures to the flower’s achromatic contrast, and illustrates how flower anatomy and background are important mediating factors. We discuss our findings in the context of the often-assumed dichotomy between detection and discrimination, chromatic versus achromatic vision, and the evolution of floral visual signals.